Prevention of oral cross-infection by using povidone-iodine compared with other antiseptic agents for orally transmitted diseases: A Review - Alaa Saif Alqhtani; Abdulkarem Ali Ali Mohammed; Farouk Al-ghazaly; Ahmed Alareqi; Anis Irmawati (Knowledge Dynamics, 2024)
The oral cavity is a high-risk infective site, and highly contagious diseases like viral infections are confirmed to be transmitted through it. Oral rinses are a very important and one of the most important objective methods and topical essential strategies to decrease the spread and transmission of contagious diseases. There is a gap in the literature regarding a comprehensive comparison between povidone-iodine and other formulations in terms of their effectiveness in preventing oral cross-infection and transmission of orally transmitted diseases. The authors performed a comprehensive literature review utilizing Google Scholar, PubMed, and Science Direct to review relevant studies over the previous years on the effectiveness of povidone-iodine in preventing oral cross-infection and transmission of orally transmitted diseases by using these keywords: oral transmitted diseases, povidone-iodine, cross-infection, and antiseptic. This article includes a comprehensive overview of the existing knowledge regarding the effectiveness of povidone-iodine compared with other antiseptic agents in preventing oral cross-infection and transmission of orally transmitted diseases. Povidone-iodine has shown effective antiseptic properties in the oral cavity without disrupting its natural balance. It is a valuable anti-septic preventive oral-transmitted disease for patients and healthcare providers, and there is no evidence to show the side effects over a long time. Povidone-iodine can be safely used as antisepsis for the oral cavity for the prevention of orally transmitted diseases as personal prophylaxis, and it's the most effective mouth rinse for viral infection in the oral cavity due to its fast action.